Après la révolution : les éditeurs lilliputiens polonais et leur offre dans les années 2016–2020 - Natalia Paprocka; Katarzyna Biernacka-Licznar (Romanica Wratislaviensia)
In the years 2000–2015, sixteen publishers, called the “Lilliputians”, revolutionised the Polish children’s book market by offering innovative works by avant-garde authors and illustrators. Translations, which represented more than two-thirds of their offer, played a crucial role in this process.